Synthesis and reactivity of selenium functionalised allylidynes and propargylidynes. Issue 41 (1st October 2018) - Hill, Anthony F.; Manzano, Richard A.; Ward, Jas S.
Abstract : The reactions of the trimethylsilylpropargylidyne [W(CCCSiMe3 )(CO)2 (Tp*)] (1 : Tp* = hydrotris(dimethylpyrazolyl)borate) towards selenium centred reagents when treated with tetrabutylammonium fluoride (TBAF) were explored in order to prepare alkynylselenolato propargylidynes, e.g., [W(CCCSePh)(CO)2 (Tp*)]. Abstract : The reactions of the trimethylsilylpropargylidyne [W(CCCSiMe3 )(CO)2 (Tp*)] (1 : Tp* = hydrotris(dimethylpyrazolyl)borate) towards selenium centred reagents when treated with tetrabutylammonium fluoride (TBAF) were explored in order to prepare alkynylselenolato propargylidynes, e.g., [W(CCCSePh)(CO)2 (Tp*)]. Treating1 with TBAF and PhSeSePh resulted in E and Z isomers of the vinylcarbyne (allylidyne) complex [W{CC(SePh)CHSePh}(CO)2 (Tp*)] in addition to traces of the trisubstituted derivative [W{CC(SePh)C(SePh)2 }(CO)2 (Tp*)]. Reactions with PhSeCl resulted in the isolation of bimetallic bis-substituted allylidyne complex [(Tp*)(CO)2 WCC(SePh)C(SePh)CCCW(CO)2 (CO)2 (Tp*)] as well as the desired selenolatopropargylidyne [W(CCCSePh)(CO)2 (Tp*)].